AGAINST THE ODDS: STRENGTHS DISPLAYED BY ABUSED WOMEN - Slabbert, Ilze (Social Work/Maatskaplike Werk, 2014)
Although legislation protecting women’s rights in South Africa is well developed, statistics indicate that violence against women has become the norm. There are no cultural, socio-economic, political, religious or educational boundaries to domestic violence. Despite this, some abused women display certain strengths. The strengths perspective is thus a suitable theoretical approach for this qualitative study exploring and describing the strengths of twenty abused women who formed the sample. Five strengths – namely hope, resilience, pride, healing and wholeness, and lastly personal qualities, traits and virtues – were identified. Some recommendations are made about the suitability of the strengths perspective for practice.